Methods, Procedures, and Techniques for Extreme Ultra-High-Speed Optimizing of Language Systems Analysis for the Amelioration of Signal-to-Noise Ratio and Comprehension Band-width between Transmitter and Receiver in the Propagation, Propulsion, and Radiation of Verbal Communication or "How to Debug Your Writing and Speech." - Bergen, Harold A. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
Speeches and compositions often become mere word lists, obscuring the message's true meaning with too many words. This paper shows that the words "use,""of," and "it" can be eliminated from writing and speech, making communications shorter, more understandable, and more efficient. Examples are provided. (RL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Communication Skills; Communication (Thought Transfer); Efficiency; Language Usage; Speech Communication; Speech Skills; Writing Skills; Reports, Research